2020
DOI: 10.1002/ccd.29287
|View full text |Cite
|
Sign up to set email alerts
|

Common carotid artery endovascular clamping for neuroprotection during carotid stenting: Flow‐gate system as an innovative treatment approach

Abstract: Objectives: We here report our clinical experience in CAS management through common carotid artery endovascular clamping with FlowGate2 system. Methods: Forty-five patients were enrolled with de novo asymptomatic internal carotid artery stenosis ≥70%. Cerebral protection during the stenting procedure was achieved using a unique endovascular clamping technique developed in our Institution which includes: (a) the occlusion of the common carotid artery only, through inflatable balloons integrated in the FlowGate2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Darganzanli et al 8 reported a 1% periprocedural stroke rate using the Concentric BGC (Stryker Neurovascular) with intermittent pump aspiration. 7,8 A preference for the Walrus BGC at our institution came from experience with its versatility, navigability, and stability. We did not experience difficulties even in challenging bovine and type III arches.…”
Section: Discussion Key Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Darganzanli et al 8 reported a 1% periprocedural stroke rate using the Concentric BGC (Stryker Neurovascular) with intermittent pump aspiration. 7,8 A preference for the Walrus BGC at our institution came from experience with its versatility, navigability, and stability. We did not experience difficulties even in challenging bovine and type III arches.…”
Section: Discussion Key Resultsmentioning
confidence: 99%
“…Flow reversal can be performed with BGCs alone by allowing back bleeding or by active aspiration, as seen in this study, or by constructing a closed system through cannulation of a vein. 7,8 In all these, the flow is reversed by a difference in pressure. These techniques are not novel because they have been explored by pioneers developing protection systems for CAS.…”
Section: Discussion Key Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the majority of our cases (90%), we opted to cross the occluded carotid artery and deploy a stent for recanalization. The use of BGCs has been described for CAS, and the usefulness of this catheter resides in its key ability to allow flow arrest to occur while the area of proximal occlusion is traversed and the stent is deployed, which prevents showering of emboli from the area of stenosis and plaque into the distal cerebral vasculature 22 23. Treatment of tandem occlusions is riskier due to the blind navigation across the occluded carotid artery, unlike in cases of carotid stenosis 24.…”
Section: Discussionmentioning
confidence: 99%